PbZrTiO3 ferroelectric oxide as an electron extraction material for stable halide perovskite solar cells. Issue 2 (5th December 2018) - Pérez-Tomas, Amador; Xie, Haibing; Wang, Zaiwei; Kim, Hui-Seon; Shirley, Ian; Turren-Cruz, Silver-Hamill; Morales-Melgares, Anna; Saliba, Benedicte; Tanenbaum, David; Saliba, Michael; Zakeeruddin, Shaik Mohammed; Gratzel, Michael; et al.
Abstract : Ferroelectric oxides as new electron extraction layers. Abstract : State-of-the-art halide perovskite solar cells employ semiconductor oxides as electron transport materials. Defects in these oxides, such as oxygen vacancies (Ovac ), act as recombination centres and, in air and UV light, reduce the stability of the solar cell. Under the same conditions, the PbZrTiO3 ferroelectric oxide employs Ovac for the creation of defect-dipoles responsible for photo-carrier separation and current transport, evading device degradation. We report the application of PbZrTiO3 as the electron extraction material in triple cation halide perovskite solar cells. The application of a bias voltage (poling) up to 2 V, under UV light, is a critical step to induce charge transport in the ferroelectric oxide. Champion cells result in power conversion efficiencies of ∼11% after poling. Stability analysis, carried out at 1-sun AM 1.5 G, including UV light in air for unencapsulated devices, shows negligible degradation for hours. Our experiments indicate the effect of ferroelectricity, however alternative conducting mechanisms affected by the accumulation of charges or the migration of ions (or the combination of them) cannot be ruled out. Our results demonstrate, for the first time, the application of a ferroelectric oxide as an electron extraction material in efficient and stable PSCs. These findings are also a step forward in the development of next generation ferroelectric oxide-based electronic and optoelectronic devices.